Ontology development of metacognitive support system for novice programmers (MSSNP) - Mohd Rum, S.N.; Ismail, M.A. (2014)
Learning and teaching computer programming have been acknowledged as being difficult and challenging. The metacognitive learning environment is needed for learning success in Computer Programming problem solving. In designing a support learning tool, the main principal of the instructional approach is to support metacognitive ability. Ontology has gained popularity in building E-learning, in which the formalism of ontology-based description can be achieved, thus giving a specification domain scope and offering an effective reuse of software patterns and systems of patterns. As there is no exact methodology for developing ontologies, here, in this paper, we present an approach for the development of MSSNP Ontology based on the general criteria and issues to be considered.